8
$\begingroup$

How can you derive that $$ \sum\limits_{n=1}^{\infty} \frac{n}{3^n} = \frac{3}{4} \, ?$$ I suspect some clever use of the geometric series will do, but I don't know how.

$\endgroup$
  • 4
    $\begingroup$ Compare to the same expression where you substitute $n-1$ for $n$. $\endgroup$ – Yves Daoust Feb 6 '17 at 7:55
  • 1
    $\begingroup$ See this. $\endgroup$ – David Mitra Feb 6 '17 at 8:36
9
$\begingroup$

We can proceed with generating functions. The trick initially seems a little contrived, but it can be made rigorous, and I think that the more you see it the more it makes sense. The first implication comes from differentiation. $$\frac{1}{1-x}=\sum_{n=0}^{\infty} x^n \implies \frac{1}{(1-x)^2}=\sum_{n=0}^{\infty}n \cdot x^{n-1}$$

So we can multiply by $x$ to get

$$\frac{x}{(1-x)^2}=\sum_{n=0}^{\infty} n \cdot x^n=\sum_{n=1}^{\infty}n \cdot x^n.$$

Substituting $x=1/3$, we obtain

$\frac{1/3}{(2/3)^2}=3/4$

$\endgroup$
2
$\begingroup$

Let $$S_n= \sum_{n=1}^{\infty} \frac{n}{3^n}\tag1$$ $$\frac13S_n=\sum_{n=1}^{\infty} \frac{n}{3^{n+1}}=\sum_{n=1}^{\infty} \frac{n+1}{3^{n+1}}-\sum_{n=1}^{\infty}\frac1{3^{n+1}}\tag2$$

$(1)-(2)$, $$\begin{align}\frac23S_n&=\sum_{n=1}^{\infty} \frac{n}{3^n}-\sum_{n=1}^{\infty} \frac{n+1}{3^{n+1}}+\sum_{n=1}^{\infty}\frac1{3^{n+1}}\\ &=\sum_{n=1}^{\infty} \frac{n}{3^n}-\sum_{n=2}^{\infty} \frac{n}{3^{n}}+\sum_{n=1}^{\infty}\frac1{3^{n+1}}\\ &=\frac13+\sum_{n=1}^{\infty}\frac1{3^{n+1}}\\ &=\sum_{n=1}^{\infty}\frac1{3^{n}}=\frac12\end{align}$$

Thus, $$S_n=\frac34$$

$\endgroup$
  • $\begingroup$ 1. No $S_n$ actually depends on $n$. 2. The justification of the step $(1)-(2)$ requires to know beforehand the series converges. $\endgroup$ – Did Aug 11 '18 at 16:55
2
$\begingroup$

Take a geometric series with term $r$ and take derivative with respect to $r$ both sides:

$\frac{d}{dr}\sum_{n=0}^{\infty}r^n=\frac{d}{dr}\frac{1}{1-r}.$

Derivate,

$\sum_{n=0}^{\infty}nr^{n-1}=\frac{1}{(1-r)^2}.$

At the left hand side, for $n=0$ the term is zero, so we can start the sum at $n=1$, and also multiply $r$ both sides to balance the exponent:

$r\sum_{n=1}^{\infty}nr^{n-1}=r\frac{1}{(1-r)^2}.$

Now you have

$\sum_{n=1}^{\infty}nr^{n}=\frac{r}{(1-r)^2}.$

For $r=\frac{1}{3}$,

$\sum_{n=1}^{\infty}n\left(\frac{1}{3}\right)^{n}=\frac{\frac{1}{3}}{\left(1-\frac{1}{3}\right)^2}.$

Operate,

$\sum_{n=1}^{\infty}n\frac{1}{3^n}=\frac{\frac{1}{3}}{\frac{4}{9}}=\frac{3}{4}.$

$\endgroup$
1
$\begingroup$

Consider the geometric series $\sum_{n=0}^\infty x^k=\frac{1}{1-x}$ for $0<x<1$.

Take the derivative with respect to $x$ on both sides. This leads to

\begin{align*} \sum_{n=1}^{\infty}nx^{n-1}&=\frac{1}{(1-x)^2}\qquad |\cdot x\\ \sum_{n=1}^\infty nx^n&=\frac{x}{(1-x)^2} \end{align*}

Setting $x=\frac{1}{3}$ gives the desired result.

$\endgroup$
1
$\begingroup$

$$\sum_{n=1}^{\infty} \frac{n}{3^n} = \sum_{n=1}^{\infty}\sum_{k=n}^{\infty}\frac{1}{3^n}\frac{1}{3^{k-n}}=\\ =\sum_{n=1}^{\infty}\frac{\left(\frac{1}{3}\right)^n}{1-\frac{1}{3}}=\frac{3}{2}\sum_{n=1}^{\infty}\left(\frac{1}{3}\right)^n =\\ = \frac{3}{2}\frac{\frac{1}{3}}{1-\frac{1}{3}} = \frac{3}{2}\frac{1}{2}=\frac{3}{4}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.